2021
DOI: 10.3389/fnins.2021.686932
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Relative Corneal Refractive Power Shift and Axial Growth in Myopic Children: Orthokeratology Versus Multifocal Contact Lens

Abstract: PurposeTo determine if the spatial distribution of the relative corneal refractive power shift (RCRPS) explains the retardation of axial length (AL) elongation after treatment by either orthokeratology (OK) or multifocal soft contact lenses (MFCLs).MethodsChildren (8–14 years) were enrolled in the OK (n = 35) or MFCL (n = 36) groups. RCRPS maps were derived by computing the difference between baseline and 12-month corneal topography maps and then subtracting the apex values. Values at the same radius were aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…YangXY et al [ 13 ] demonstrated that a smaller X50 is significantly associated with smaller ALG in children wearing orthokeratology lenses with different peripheral curves. FanJ et al [ 34 ] reported that contact lenses with smaller Half_x induce RCRPS closer to the corneal center may exert better myopia control. The other is corneal asymmetry [ 9 , 35 ] which could be well quantified by the amplitude of a sinewave running one cycle over 360 degrees around the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…YangXY et al [ 13 ] demonstrated that a smaller X50 is significantly associated with smaller ALG in children wearing orthokeratology lenses with different peripheral curves. FanJ et al [ 34 ] reported that contact lenses with smaller Half_x induce RCRPS closer to the corneal center may exert better myopia control. The other is corneal asymmetry [ 9 , 35 ] which could be well quantified by the amplitude of a sinewave running one cycle over 360 degrees around the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with history of Ortho-K lens wear, contact lens contraindications, related eye systemic diseases, uncorrected visual acuity below 20/25, or unacceptable lens decentration (over 1 mm) after regular wear were excluded. These inclusion and exclusion criteria, along with details of the clinical care adopted, follow those presented in our earlier clinical study [ 27 ]. The study was approved by the Ethics Committee of the eye hospital and complied with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the Dreamlite lenses were manufactured with the Boston XO hexafocon-A material that had Dk of 100 × 10 –11 (cm 2 s −1 ) (mLO 2 ml −1 × mmHg). The lenses were fitted to both eyes by an experienced clinician (JJ) according to the manufacturer's guidelines, and participants were requested to wear the lenses for eight hours each night except in cases of illness or abnormal ocular symptoms [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have attempted to quantitatively assess the effectiveness of Ortho-K for AL control based on the defocus characteristics produced during the treatment. However, the methods of existing studies remain incomprehensive as they consider only certain axis directions [12,13], specific regions [14,15] or profiles [16] and do not fully reflect the morphology of the cornea in its entirety and the overall defocus characteristics in a three-dimensional space. In addition, it has been demonstrated that Ortho-K for myopia control significantly increases the Zernike coefficients and ocular higher-order aberrations in children [17,18].…”
Section: Introductionmentioning
confidence: 99%